High Interfacial‐Energy and Lithiophilic Janus Interphase Enables Stable Lithium Metal Anodes. Issue 36 (29th July 2021) - Li, Guoxing; Liu, Shipeng; Liu, Zhe; Zhao, Yingjie
Abstract: The stability of solid electrolyte interphase (SEI) layers is critical for developing lithium (Li) metal batteries. However, the fabrication of stable SEI layers is plagued by un‐controlled structures, properties, and functions. Here a controllable design of an ordered LiF‐rich and lithiophilic hybrid Janus interphase (LiF‐HJI) is reported using organic fluorination reagent as a functional SEI precursor. The LiF‐HJI with a lower crystalline LiF layer and an upper Li organosulfide layer provides high interfacial energy with the Li metal and strong Li‐ion affinity, allows homogenous Li‐ion distribution, fast and uniform Li‐ion transport, and excellent mechanical and passivation properties, enabling stable Li metal anodes under harsh conditions, such as high deposition capacities (6 mA h cm −2 ), current densities (10 mA cm −2 ), and rates (5 C). Stable LiF‐HJI@Li greatly improves cycling stability and capacity retention (80.1% after 300 cycles) of Li||LiNi0.8 Co0.1 Mn0.1 O2 cells at a commercial‐level areal capacity (≈ 4.2 mA h cm −2 ). Even under a lean‐electrolyte condition of 3 g Ah −1, 80% capacity retention can be maintained after 100 cycles, demonstrating excellent cycling performance under such harsh conditions. Abstract : A controllable design of an ordered LiF‐rich organic/inorganic hybrid Janus interphase (LiF‐HJI) for high‐performance Li metal anodes is reported. LiF‐HJI with high solid electrolyte interphase/Li interfacial energy and strong Li‐ion affinity allows homogenous Li‐ion distribution, fast and uniform Li‐ion transport, and excellent mechanical and passivation properties, enabling stable Li metal anodes under harsh conditions.